Social Participation in the Elaboration Process of the Regional Tourism Policy of Arica and Parinacota 2012-2016 - Godoy Flores, Iván (Revista del CLAD Reforma y Democracia, 2019)
This document presents the result of an analysis on the elaboration of the Regional Tourism Policy of Arica and Parinacota 2012-2016 (in Chile) focused on the participation of relevant actors during technical, social and political validation instances. An epistemological implication is described based on a set of obstacles, conflicts, resistance and adversities found in making this policy, chosen as a case study for “policy network”, to allow its understanding and importance as one of the first experiences of decentralization of sectoral decisions in the region. Through the analysis of its content and semi-structured interviews, the work approached the causes -often the defense of economic and ideological interests- of the conflicts arising in the elaboration of a regional policy.
Keywords: Citizen Participation; Social Participation; Policies Planning; Policies Formulation; Regional Policy; Tourism Policy; Case Analysis; Chile